Aggregation and the Estimated Effects of Local Economic Conditions on Health - Jason M. Lindo (Institute for the Study of Labor (IZA), 2013)
This paper considers the relationship between local economic conditions and health with a focus on different approaches to geographic aggregation. After reviewing the tradeoffs associated with more- and less-disaggregated analyses - including an investigation of the migratory response to changing economic conditions - I update earlier state-level analyses of mortality and infant health and then consider how the estimated effects vary when the analysis is conducted at differing levels of geographic aggregation. This analysis reveals that more-disaggregated analyses severely understate the extent to which downturns are associated with improved health. Further investigation reveals that county economic conditions have an independent effect on mortality but that state and regional economic conditions are stronger predictors. I also leverage county-level data to explore heterogeneity in the link between county economic conditions and health across states, demonstrating that local downturns lead to the greatest improvements in health in low-income states.
Keywords: I10; J20; E32; 330; health; recessions; mortality; infant health; Regionale Arbeitslosigkeit; Gesundheit; Sterblichkeit; Aggregation; Schätzung; USA